Potensi Cendawan Asal Tanah Perakaran Bambu Sebagai Endofit dan Agen Biokontrol Penyakit Akar Gada Pada Tanaman Brokoli - . Asniah; . Widodo; Suryo Wiyono (Universitas Lampung, 2013)
The potential of fungi from bamboo rhizosphic soils as endophytic and biocontrol agents of clubroot disease (Plasmodiophora brassicae) on Brocoli. Clubroot, caused by Plasmodiophora brassicae is a serious soilborne disease of plants worldwide, capable of severe infection on broccoli, cabbage and cauliflower. Clubroot is the most destructive diseases on cruciferae in Indonesia. The existing control measures, including biological control do not provide satisfactory result. The objective of the study was to explore fungi from bamboo rhizospheric soils as endophytic that can suppress clubroot disease in broccoli. There were two steps in this study: (1) exploration and identification of fungi from bamboo rhizospheric soils. (2) Effectiveness test of the fungi in suppressing clubroot disease. There were four species of fungi as endophytes in brocoli in this study, e.g Aspergillus sp., Mortierella sp., Paecilomyces sp., and Chaetomium globosum. They had colonized broccoli root endophytically and suppressing clubroot disease. Paecilomyces sp. of endophytic fungi can suppress clubroot diseases incidence for 18.75%.